ChemInform Abstract: Regio‐ and Stereoselective 1, 2‐Dihydropyridine Alkylation/Addition Sequence for the Synthesis of Piperidines with Quaternary Centers. Issue 34 (26th August 2014) - Duttwyler, Simon; Chen, Shuming; Lu, Colin; Mercado, Brandon Q.; Bergman, Robert G.; Ellman, Jonathan A.
Abstract This is the first example of a C‐alkylation of 1, 2‐dihydropyridines with alkyl triflates and Michael acceptors to yield products with quaternary stereocenters with high regio‐ and diastereoselectivity.